Prospective associations between joint categories of physical activity and insomnia symptoms with onset of poor mental health in a population-based cohort - Mitch J Duncan; Elizabeth G Holliday; Nicola W Burton; Nicholas Glozier; Stina Oftedal (Elsevier, 2023)
Background: Physical inactivity and insomnia symptoms are independently associated with increased risk of depression and anxiety; however, few studies jointly examine these risk factors. This study aimed to prospectively examine the joint association of physical activity (PA) and insomnia symptoms with onset of poor mental health in adults. Methods: Participants from the 2013 to 2018 annual waves of the Household Income and Labour Dynamics in Australia panel study who had good mental health (Mental Health Inventory-5 >54) in 2013, and who completed at least 1 follow-up survey (2014-2018), were included (n = 10,977). Poor mental health (Mental Health Inventory-5 ≤ 54) was assessed annually. Baseline (2013) PA was classified as high/moderate/low, and insomnia symptoms (i.e., trouble sleeping) were classified as no insomnia symptoms/insomnia symptoms, with 6 mutually exclusive PA-insomnia symptom groups derived. Associations of PA-insomnia symptom groups with onset of poor mental health were examined using discrete-time proportional-hazards logit-hazard models. Results: There were 2322 new cases of poor mental health (21.2%). Relative to the high PA/no insomnia symptoms group, there were higher odds (odds ratio and 95% confidence interval (95%CI)) of poor mental health among the high PA/insomnia symptoms (OR = 1.87, 95%CI: 1.57-2.23), moderate PA/insomnia symptoms (OR = 1.93, 95%CI: 1.61-2.31), low PA/insomnia symptoms (OR = 2.33, 95%CI: 1.96-2.78), and low PA/no insomnia symptoms (OR = 1.14, 95%CI: 1.01-1.29) groups. Any level of PA combined with insomnia symptoms was associated with increased odds of poor mental health, with the odds increasing as PA decreased. Conclusion: These findings highlight the potential benefit of interventions targeting both PA and insomnia symptoms for promoting mental health.